OF THE LEARNING ENVIRONMENT AND LEARNING DISCIPLINE ON LEARNING OUTCOMES IN SOCIAL STUDIES SUBJECTS CLASS VIII AT SMP MUHAMMADIYAH SAMPIT - Ifan ij Julianta (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2022)
The purpose of the study is to determine the influence of the learning environment and learning discipline on learning outcomes in social studies class VIII subjects at SMP Muhammadiyah Sampit for the 2022/2023 academic year. The subjects in this study were class VIII students from R1-R3, which had a population of 82 students, and the sample that the researchers used was 82 students, and the techniques used Nonprobability. The research instruments used are questionnaires, and documentation, as well as the analysis techniques used are with multiple Linear Regression. The results of the ex-post facto research analysis show that; (1) there is no influence of the learning environment on learning outcomes in social studies class VIII subjects at Muhammadiyah Sampit Junior High School, as can be seen from the tcount of < ttable, which is -0.371 < 1.990. (2) There is no influence of learning discipline on learning outcomes in social studies class VIII subjects at Muhammadiyah Sampit Junior High School, as can be seen from the t count of < ttable, which is 0.365 < 1.990. (3) There is no influence of the learning environment and learning discipline on learning outcomes in social studies class VIII subjects at Muhammadiyah Sampit Junior High School, as can be seen from Fcount (0.083) < Ftable (3.11).